1996
DOI: 10.1083/jcb.133.4.831
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cells express three distinct dynein heavy chains that are localized to different cytoplasmic organelles.

Abstract: Abstract. We describe two dynein heavy chain (DHC)-like polypeptides (DHCs 2 and 3) that are distinct from the heavy chain of conventional cytoplasmic dynein (DHC1) but are expressed in a variety of mammalian cells that lack axonemes. DHC2 is a distant member of the "cytoplasmic" branch of the dynein phylogenetic tree, while DHC3 shares more sequence similarity with dynein-like polypeptides that have been thought to be axonemal. Each cytoplasmic dynein is associated with distinct cellular organelles. DHC2 is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
210
2
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(229 citation statements)
references
References 46 publications
15
210
2
2
Order By: Relevance
“…The molecules that actually recruit and/or organize ␥-tubulin on Golgi membranes still remain to be identified. The assembly of ␥-tubulin onto centrosomes being mediated by cytoplasmic dynein in a MT-dependent manner (Young et al, 2000), one might even speculate that cytoplasmic dynein, which was also identified on Golgi membranes (Vaisberg et al, 1996;Roghi and Allan, 1999), might be needed to some extent for assembling and/or docking ␥-tubulin on the Golgi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecules that actually recruit and/or organize ␥-tubulin on Golgi membranes still remain to be identified. The assembly of ␥-tubulin onto centrosomes being mediated by cytoplasmic dynein in a MT-dependent manner (Young et al, 2000), one might even speculate that cytoplasmic dynein, which was also identified on Golgi membranes (Vaisberg et al, 1996;Roghi and Allan, 1999), might be needed to some extent for assembling and/or docking ␥-tubulin on the Golgi.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic and stable MTs are specialized in mediating specific transport steps (Mizuno and Singer, 1994;Poü s et al, 1998), which may involve various molecular motors, often localized on Golgi membranes (Vaisberg et al, 1996; for review see . The way such specialized motor proteins specifically interact with the appropriate target membranes is still an open question but may be related to the regulation of membrane traffic, as suggested by the example of rabkinesin-6, which binds the small GTPase Rab6 involved in Golgi-to-ER retrograde transport (Echard et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Numerous distinct dynein heavy chain genes have been isolated from Paramecium, 7 Chlamydomonas, 8,9 sea urchin, 10 rat, 11,12 mouse, 13 and human. [13][14][15][16] However, comparing the dynein heavy chain gene family in well characterised species such as sea urchin suggests that either mammals have less axonemal dynein heavy genes or that some mammal genes are still to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic dyneins are a multiprotein family of at least three members (Criswell et al, 1996;Vaisberg et al, 1996). The most abundant isoform, dynein 1, works in conjunction with a multisubunit activator protein, dynactin.…”
Section: Introductionmentioning
confidence: 99%